Adaptation of university students in time of a pandemic as social isolation (Research, Society and Development, 2021)
The Study objective is to analyze the consumption behavior, habits and attitudes of university students during the lockdown in relation to the COVID-19 pandemic. It is considered an exploratory and quantitative study. As for the sampling, the non-probabilistic for convenience was used in a total of 100 interviews, in a public and private institution in a city  of Paraná interior. The main findings were that among the interviewees, 90.4% agreed that it is important to know the procedure for cleaning food products; 85.6% agree that a company that offers delivery makes them buy more; 75.0% realized that with isolation, product advertisements increased; 70.2% always seek to buy previously acquired brands; 72.1% agree that they started to buy less in physical stores, and that, on the other hand, 64.4% started to buy more in online stores. About 42.3% agree that during the pandemic, the reliability of cafeteria/fast food hygiene decreased and only 25% agree that with social isolation, purchases of non-essential goods are more frequent. It was identified that online shopping increased due to the current scenario, which did not stop buying, but migrated more to online shopping due to the ease and practicality, thus making e-commerce continue with its flow of product sales and they demonstrated even though they are concerned with the hygiene and quality of food products when purchased.